Implementing and managing communitybased education and service learning in undergraduate health sciences programmes: Students’ perspectives - S Kruger; M Nel; G van Zyl (South African Medical Association, 2015)
Background. A current challenge in the training of healthcare professionals is to produce socially responsive graduates who are prepared for work in community settings. Community-based education (CBE) and service learning (SL) are teaching approaches used in the Faculty of Health Sciences at the University of the Free State (UFS), Bloemfontein, South Africa to address these challenges. Students have different views with regard to CBE and SL, and by surveying these perceptions information can be gained on how to better integrate CBE and SL into learning programmes. Objective. To investigate students’ perceptions of CBE and SL in a health sciences faculty. Methods. Nominal group discussion was conducted to identify topics to explore students’ perceptions of CBE and SL. A questionnaire was administered to all undergraduate health sciences students at UFS to survey their perceptions of CBE and SL. Results. Twenty different themes were identified that had a positive or negative impact on the students’ perceptions of CBE and SL. Positive aspects included personal growth, exposure to a diversity of patients, gaining practical experience and enhancement of inter- and intrapersonal skills. However, the students perceived the following as negative or inadequate: the organisation of CBE and SL; availability of resources; attitude of healthcare professionals; and prior orientation. Conclusion. CBE and SL need to be carefully implemented and managed to enhance the learning experience for students and produce socially responsive healthcare professionals who are equipped to address the healthcare challenges in their communities.